Dilema da identidade: os rataplãs do Olodum, políticas de significado e o campo etnopopular no Brasil - Edson Farias (Ciências Sociais Unisinos)
Upon the application of the figurative-procedural model, in this article, we focus on the Afro-Bahian musical band and carnival group Olodum as heuristic of the correlations between culture, politics and economics. These are triangulations through which the group has achieved national and international recognition for its recreational-artistic presentations. We discuss how, in this aesthetical presentations, policies of meaning were engaged with human rights and black cultural identities and expressions as well. Along the text, identity propositions of this cultural association are discussed in the light of the position Olodum has in the ethno-popular field, social realm in which properties of scarceness and affluence become accomplices.